2016
DOI: 10.1007/s12032-016-0797-x
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline- and trastuzumab-induced cardiotoxicity: a retrospective study

Abstract: Some chemotherapeutic agents cause cardiotoxic effects including reduction in left ventricular ejection fraction (LVEF) and occasionally congestive heart failure. Anthracyclines and HER2 monoclonal antibodies are common offenders, but clinical practice data on LVEF changes, risk factors and acute recovery is lacking. We retrospectively examined the electronic medical record at an academic medical center for receipt of anthracyclines and/or trastuzumab from 2000 to 2013 in cancer patients. Patient characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
(24 reference statements)
2
20
1
1
Order By: Relevance
“…dysfunction following high cumulative dose anthracycline therapy (e.g., doxorubicin 700 mg/m²) (32). Combination therapy with chest/mediastinal radiation or HER-2 inhibitors (e.g., trastuzumab) as commonly used in breast and gastric cancer therapy can further multiply anthracycline-induced cardiotoxic effects (33)(34)(35)(36)(37)(38)(39). Cumulative dose, intravenous bolus administration, female sex, hypertension, diabetes mellitus and known cardiovascular disease are risk factors for the development of anthracycline cardiotoxicity (5,7,32,35,40).…”
Section: Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…dysfunction following high cumulative dose anthracycline therapy (e.g., doxorubicin 700 mg/m²) (32). Combination therapy with chest/mediastinal radiation or HER-2 inhibitors (e.g., trastuzumab) as commonly used in breast and gastric cancer therapy can further multiply anthracycline-induced cardiotoxic effects (33)(34)(35)(36)(37)(38)(39). Cumulative dose, intravenous bolus administration, female sex, hypertension, diabetes mellitus and known cardiovascular disease are risk factors for the development of anthracycline cardiotoxicity (5,7,32,35,40).…”
Section: Heart Failurementioning
confidence: 99%
“…Chemotherapy protocols containing alkylating agents or anthracyclines have shown plasma troponin I elevation in 12-33% in adults (43,54,(62)(63)(64)(65) and up to 47% in children (56). The cardiotoxic effect of the human epidermal growth factor receptor 2 inhibitor (HER2 inhibitor) trastuzumab with or without anthracycline-based chemotherapy has been extensively studied as it affects a significant portion of breast cancer patients (37,38,66). Trastuzumab monotherapy caused elevated troponin I in 14% while in combination therapy of trastuzumab with anthracyclines, elevated troponin I was observed in 21-24% of patients (54,63,67).…”
Section: Troponinmentioning
confidence: 99%
“…Heart failure has been found correlated with administration of chemotherapy, which is considered as cardiotoxicity [ 2 ]. It was been reported that reduction in left ventricular ejection fraction (LVEF) was impaired in 12.5% of cancer patients receiving anthracycline/trastuzumab administration [ 3 ]. Though several mechanisms have been proposed, such as endoplasmic reticulum stress, mitochondria damage, and calcium overload [ 4 6 ], the exact molecular mechanisms of cardiotoxicity are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hamirani et al showed that the presence of arterial hypertension, hyperlipidaemia, and coronary artery disease correlates with reduced LV function in 549 patients after anthracycline or trastuzumab therapy [18] . In agreement with this study, we found that the CardTox-Score – which includes five cardiovascular risk factors – showed high predictive value for the development of CIMC in our small internal validation cohort.…”
Section: Discussionmentioning
confidence: 99%